Wellbeing Facility as a Source of Data for Sustainable Human Resource Management - Grzegorz LESZCZYNSKI; Maciej LAWRYNOWICZ; Anna ROGALA (Communications of International Proceedings, 2021)
This paper aims to identify the key aspects of wellbeing-driven expectations for facilities and then to point out its potential benefits for human resource management. It is a conceptual paper based on the identification of the role of Sustainable Human Resource Management (SHRM), characteristics of wellbeing objectives and expectations of human resource management. Based on the concept of SHRM we discuss challenges for the inclusion of facilities to that concept. The paper recognizes the increased importance of Human Resource divisions, the need for facilities that enhance their employees' wellbeing, and indicates further research directions.
Keywords: Sustainability; Wellbeing; Human Resource Management; Office Facilities; The Construction Industry